Media Monitoring Analysis of Moell Skincare's Clarification on Child Endorsement Issues in Live Streaming Marapthon During 29 March- 8April 2026 - Zulfanida Nurul Sadiyyah; Dewi Christina Marbun; Nisa Lathifah; Shinta Hartini Putri; Aulia Agistiyani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines media monitoring of Moell Skincare's clarification regarding the issue of child endorsement in Live Streaming Marapthon during March 29-April 8, 2026. The controversy emerged following the involvement of Andrew Raxy Neil, the son of public figure Erika Carlina, whose collaboration with Moell Skincare became associated with the program and generated extensive discussions on social media. This study aims to analyze the dynamics of public conversations following the brand's clarification. A qualitative descriptive approach using netnography was employed. Data were collected through non-participant observation using the Brand24 social media monitoring platform. The analysis focused on conversation volume, issue reach, public sentiment, dominant platforms, influential actors, and discussion themes. The findings recorded 256 mentions, with a social media reach of 12 million and a non-social media reach of 1 million. Positive sentiment dominated the conversations (65%), while negative sentiment accounted for 35%. TikTok and X emerged as the primary platforms, contributing 46.7% and 43.8% of total conversations, respectively, while online news media accounted for 9.5%. The dominant themes included child involvement in digital activities, the collaboration between Moell Skincare and Andrew Raxy Neil, the brand's clarification, and public responses to the controversy. The findings demonstrate that public conversations surrounding Moell Skincare's clarification were shaped by various actors, platforms, sentiments, and themes within digital environments. Media monitoring provides valuable insights into how organizational issues and brand clarifications develop across social media platforms.